ANALYSIS OF WALL SHAPE IN INDOOR AIR CIRCULATION BY THE FINITE ELEMENT METHOD - Drach, P. R. C.; Karam F., J. (Revista de Engenharia Térmica, 2007)
The use of computational models in built environments comes from the need to deal with situations as close as possible to the reality and also to study functional spaces that could be able to provide, for example, thermal comfort. In this work we analyze some cases of indoor air circulation in built environments through a mixed stabilized finite element method, applied to the Navier-Stokes equations in velocity and pressure variables. The implemented numerical method ensures stability for the internal constraint imposed by the velocity field, and accommodates moderate to large advective effects. The obtained internal wind field allows the choice of wall shapes that increase or not the ventilation and can alter its distribution, allowing in this way a better adequacy of the built environment for the climate needs and its objectives.